ANALISIS PENDAPATAN DAN EFISIENSI TEKNIS USAHATANI HORENSO KELOMPOK TANI AGRO SEGAR KECAMATAN PACET KABUPATEN CIANJUR JAWA BARAT - Ekaningtias, Decy; Daryanto, Heny Kuswanti Suwarsinah (Forum Agribisnis, 2013)
Vegetable is one of agricultural commodities that has potential related with economic value. Nowadays, business in vegetable field especially Japanese vegetable is beginning to develop. A large number of Japanese restaurant in Jabodetabek becomes a big opportunity for surrounding Japanese vegetable farmer to become supplier. One of Japanese vegetable that widely consumed and now beginning to attract horticultural farmers is Horenso. Agro Segar Farmers Group is one of the farmers group in Cianjur that cultivate Japanese vegetable include Horenso. The income from Japanese vegetable is more profitable than other commodities and demand from Japanese restaurants and hotels in Jabodetabek are also quite high. Horenso demand that reached 70 kilogram per day requires an adequate supply in everyday. Highly demand of Horenso with limited land ownership and production takes an efficient production methods in order to optimize crop yields per unit area of land and also maximize farm income. The purposes of this research are to analyze farmers income in Agro Segar Farmers Group and to analyze technical efficiency of Horenso cultivation. Income analysis applied using R/C ratio andÂ frontier production function applied using MLE estimation procedure with assuming that Cobb Douglas is a functional form of production function in this research. The result from R/C ratio is 2,79 and 2,72. It shows that farmerâs income in Agro Segar Farmers Group is profitable. Seed and pesticide have a negative effect on production function. Farmerâs age, experience, counseling dummy and land ownership dummy have a positive effect on technical inefficiency.